Rehabilitation Management of the Charcot–Marie–Tooth Syndrome: A Systematic Review of the Literature. Issue 17 (April 2016) - Corrado, Bruno; Ciardi, Gianluca; Bargigli, Chiara
Abstract : Abstract: The Charcot–Marie–Tooth disease (CMT) causes significant muscular deficits in the affected patients, restricts daily activities (ADL), and involves a severe disability. Although the conservative intervention is the only treatment for the disease, there is no scientific evidence so far on rehabilitation treatment. Objectives of the review are: research the best literary evidence so far on the rehabilitation treatment of CMT; critically analyze the outcome, to build an evidence-based work protocol. A systematic review of the rehabilitation of a patient with CMT, including the results from the following databases: Pubmed, Medline, Embase, Pedro, Cinahl, Ebsco discovery. Criteria for inclusion: randomized/controlled studies, analytic studies, transversal studies on a cohort of at least 10 individuals; medium/long-term report of the results. Eleven studies in total have been admitted to the final review phase; trials about physiotherapy CMT treatment (5), about orthosis treatment (6). Despite the wide range of outcomes and proposed interventions, the data points to the following: strength or endurance trainings improve functionality and ADLs of affected patients, while orthotic role is, at the moment, not completely clear. Physiotherapy treatment is a useful tool to manage CMT; more studies on a larger number of cases are needed to define orthosis utility and to establish the gold standard of the treatment.